Enhancing spatiotemporal reconstructions of hydroclimate variability across the Mediterranean during the last millennium - Kevin J. Anchukaitis; Ramzi Touchan; David M. Meko; Dalila Kherchouche; Sai͏̈d Slimani; Fatih Sivrikaya; Rachid Ilmen; Ιoannis Mitsopoulos; Jean Stephan; Jihad Attieh; Foued Hasnaoui; J. Julio Camarero; et al. (Springer Science and Business Media LLC, 2023)
Abstract
The Mediterranean region is projected to experience severe drying trends and more extreme hydroclimate events as a consequence of anthropogenic climate change over the next century. In some places this signal may have already emerged from natural variability. Here we provide context for recent and future changes with a new high-resolution (0.5$^o$) spatial reconstruction of the Palmer Drought Severity Index (PDSI) using a tree-ring network that spans much of the last millennium. This network provides new information that extends and enhances the existing Old World Drought Atlas (OWDA), and we identify and attribute the differences between the OWDA and our reconstruction. We also reexamine previous conclusions about the severity of recent drought in the context of earlier centuries. We find that, in both the western Mediterranean and the Levant, recent dry periods are indeed the worst in at least the last 500 years, but our assessment of the significance and uncertainty of this finding is affected by differences in the tree-ring networks used for the reconstructions. Long millennium-length hydroclimate reconstructions in the Mediterranean provide the opportunity to understand variability and trends in the hydroclimate of the region, while extant uncertainties arising from the existing tree-ring chronology network and methodological choices call attention to locations that require further proxy collection and statistical scrutiny.
Keywords: Atmospheric Science; Physical geography; Dendrochronology; Ecosystem Resilience; Evolutionary biology; Context (archaeology); Machine learning; Paleoclimatology; Biology; Climatology; Global and Planetary Change; Drought; Geography; Global Forest Drought Response and Climate Change; Causes and Impacts of Climate Change Over Millennia; Extant taxon; Proxy (statistics); Geology; FOS: Earth and related environmental sciences; Computer science; Earth and Planetary Sciences; Archaeology; Physical Sciences; Global Drought Monitoring and Assessment; Environmental Science; Global Vegetation Models; Mediterranean climate; 14. Life underwater; 15. Life on land; 6. Clean water; 13. Climate action